Parkinson's Disease: What Can Retinal Imaging Tell Us? - Mariachiara Di Pippo; Sergio d’Agostino; Francesco Ruggeri; Chiara Carrozzi; Davide Fasciolo; Solmaz Abdolrahimzadeh (Journal of Integrative Neuroscience, 2024)
Parkinson’s disease (PD) is a neurodegenerative disorder characterized by motor symptoms such as tremors, rigidity, and bradykinesia. While the diagnosis of PD primarily relies on clinical assessments and neurological examination, there has been growing interest in exploring non-invasive imaging techniques to aid in early detection and monitoring of the disease. In recent years, retinal imaging has emerged as a promising tool for studying PD due to the close anatomical and functional similarities between the retina and the brain. Retinal imaging methods, such as spectral domain optical coherence tomography and optical coherence tomography angiography, enable non-intrusive visualization and measurement of retinal structures and blood vessels. These techniques hold the promise of capturing alterations in retinal structure and function that could potentially mirror the underlying pathological mechanisms in PD. This review article aims to provide an overview of the current understanding of retinal changes in PD and the potential utility of retinal imaging as a diagnostic and monitoring tool.